Production and Digital Image Correlation Analysis of Titanium Foams with Different Pore Morphologies as a Bone-Substitute Material. (3rd February 2019) - Shbeh, Mohammed; Oner, Elif; Al-Rubaye, Ammar; Goodall, Russell
Abstract : Ti foams are mesoporous structured materials that are characterized by their high surface area and interconnected porosity with a huge potential for biomedical applications. In this study, we investigated the production of titanium foams with different pore morphologies as a bone-substitute material via the addition of different amounts, shapes, and sizes of the space holder. Furthermore, we also carried out strain analysis using digital image correlation (DIC) in order to analyse the strain distribution across the porous samples. In addition, the nature of the relationship between the amount of the space holder added and final amount of porosity in the foams produced was also examined. The results demonstrated that the relationship between the space holder amount and porosity in the samples follows a complex one-phase exponential decay function in an increasing form. Our findings also suggest that the shape of the space holder does not play a significant role in dictating the porosity of the foams produced in the current study. However, the space holder's shape does have a substantial role in dictating the mechanical properties of the foams produced, where Ti foams produced using a cubic or irregular space holder were found to have a lower yield stresses than those made with the spherical space holder.